Identification of Aglaonema Ornamental Plants in Tonggolobibi Village, Sojol Sub-District and its Utilization as Learning Media - Wanty Aprilianti; Mohammad Jamhari; Lestari M.P. Alibasyah (CV. Dharma Samakta Edukhatulistiwa, 2025)
This research aims to describe the types of Aglaonema ornamental plants found in Tonggolobibi Village and to make a Pocket Book that is suitable for use as a learning medium about the types of Aglaonema ornamental plants. This type of research is Descriptive Qualitative research with data collection techniques in the form of exploration or exploration and documentation using the Purposive Sampling method. Population and Samples in this study are the total number of Aglaonema ornamental plant species found in Tonggolobibi Village, Sojol District. The results of research that has been done, obtained as many as 22 types of Aglaonema ornamental plants in Tonggolobibi Village, Sojol District. The results of this study can be used as learning media in the form of Pocket Books by obtaining a feasibility percentage value of 87.2% or rounded up to 87%. From the results of this assessment, based on the eligibility criteria according, it can be concluded that this Pocket Book is very feasible to use as a learning medium.